2006
DOI: 10.1152/ajpendo.00047.2006
|View full text |Cite
|
Sign up to set email alerts
|

The vascular endothelial cell mediates insulin transport into skeletal muscle

Abstract: The pathways by which insulin exits the vasculature to muscle interstitium have not been characterized. In the present study, we infused FITC-labeled insulin to trace morphologically (using confocal immunohistochemical methods) insulin transport into rat skeletal muscle. We biopsied rectus muscle at 0, 10, 30, and 60 min after beginning a continuous (10 mU·min−1·kg−1), intravenous FITC-insulin infusion (with euglycemia maintained). The FITC-insulin distribution was compared with that of insulin receptors (IR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(137 citation statements)
references
References 36 publications
12
123
0
2
Order By: Relevance
“…idly enters the vascular endothelial cell of skeletal muscle (within 10 min) and is then concentrated in the cell (60 min) to be slowly released from the abluminal side (19). Their results demonstrated a slow traversal of insulin across the vascular wall, which supports the delayed transendothelial transport hypothesis.…”
Section: Fig 4 Average Time Course Of Net (Injected Leg Corrected Fmentioning
confidence: 72%
See 1 more Smart Citation
“…idly enters the vascular endothelial cell of skeletal muscle (within 10 min) and is then concentrated in the cell (60 min) to be slowly released from the abluminal side (19). Their results demonstrated a slow traversal of insulin across the vascular wall, which supports the delayed transendothelial transport hypothesis.…”
Section: Fig 4 Average Time Course Of Net (Injected Leg Corrected Fmentioning
confidence: 72%
“…Our laboratory and others have reported that the transcapillary transport of insulin is not saturable in vivo (15,18). Barrett et al (19) have recently imaged the endothelial transport process and showed that fluorescently labeled insulin is rapidly taken up and con-centrated in endothelial cells, which suggests that transit to the interstitium may be rate limiting. However, Clark and colleagues have suggested that insulin mediates multiple hemodynamic changes in the vasculature before acting on skeletal muscle, which could also account for the delay in insulin action (20,21).…”
Section: Research Design and Methods-intramuscular Injections Of Salimentioning
confidence: 86%
“…Capillary endothelium contains gaps between cells, and there is evidence that IGFs utilise this paracellular pathway (Bastian et al 1997). Insulin traverses the endothelium by a transcytotic pathway that involves insulin and IGF1 receptors (Wang et al 2006), so it remains possible that IGFs also utilise this pathway. Binary complexes containing IGFs and IGFBPs can traverse the endothelium and the latter have a role in regulating this process (Boes et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reported K d value of insulin for its receptor in primary rat alveolar epithelial cells is approximately 2.0ϫ10 Ϫ3 mg/ml, 20) which is quite different from the K m value observed in this study. Wang et al 21) suggested that insulin-like growth factor-I (IGF-I) receptor as well as insulin receptor may mediate insulin transport in endothelial cells in a process involving caveolae. However, no effect of nystatin, a caveolae-mediated endocytosis inhibitor, was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%